1985
DOI: 10.1144/gsl.qjeg.1985.018.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater abstraction from Basement Complex areas of Africa

Abstract: Summary The Basement Complex of Africa is a heterogeneous mixture of crystalline rocks, predominantly of a granitic or gneissose character. Groundwater occurs within these crystalline rocks in fissures or in the superficial weathered zones. The rocks are relatively impermeable and groundwater can occur in the superficial deposits overlying the bedrock. There are no regional aquifers in Basement Complex country and each site has to be treated as unique. The occurrence of groundw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 11 publications
0
42
0
Order By: Relevance
“…As a result, certain assumptions had to be made in order to determine the extent to which these lineaments influence or relate to borehole productivity in the Limpopo Province on a regional scale. According to Braathen and Gabrielsen (1998) a large lineament can enhance fracturing up to 300 m away while Clark (1985) suggested that the area of influence might be less than 150 m and Fernandes and Rudolph (2001) reduced it further to 70 m in their studies. Considering the spatial margin, all boreholes within 150 m of a lineament were considered to be targeting a lineament in this study.…”
Section: Lineament Analysismentioning
confidence: 98%
“…As a result, certain assumptions had to be made in order to determine the extent to which these lineaments influence or relate to borehole productivity in the Limpopo Province on a regional scale. According to Braathen and Gabrielsen (1998) a large lineament can enhance fracturing up to 300 m away while Clark (1985) suggested that the area of influence might be less than 150 m and Fernandes and Rudolph (2001) reduced it further to 70 m in their studies. Considering the spatial margin, all boreholes within 150 m of a lineament were considered to be targeting a lineament in this study.…”
Section: Lineament Analysismentioning
confidence: 98%
“…Fractured crystalline bedrocks remain good sources for drinkable water but sitting of highly productive wells in these rock units remains a challenging and expensive task because fractured developments on regional scale are both heterogeneous and anisotropic. Also fractured and viable aquifers wholly within the fractured bedrock are of rare occurrence because of the typically low storability of fracture systems [6]. The availability of groundwater in these aforementioned rocks is largely due to the development of secondary porosity and permeability resulting from weathering and fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, groundwater potentials have been evaluated based on consideration of important parameters such as overburden thickness, weathered layer resistivity, bedrock resistivity, aquifer layer resistivity and aquifer layer thickness among others [6]- [13] and each parameter is considered in isolation. However in this study a multi-criteria GRT modelling approach was developed for evaluating groundwater potential in a typical basement complex environment.…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline basement rock in Africa is primarily of Precambrian age and granitic or gneissose in type (Clark, 1985). Basement aquifers are formed due to the effects of prolonged weathering and tectonic forces on the parent rock (Fookes, 1997).…”
Section: Introductionmentioning
confidence: 99%